Agronomy of cassava: IITA research guide, No. 60 - Ekanayake, I.J.; Osiru, D.; Porto, M. (1997)
Even though cassava is a durable crop, it has certain husbandry requirements and is responsive to favorable crop management practices. Healthy, fresh stem cuttings from mature cassava plants are the best planting materials. Depending on moisture conditions of the soil, farmers plant cassava cuttings vertically, at an angle, or horizontally. Slow initial development of sprouts makes cassava susceptible to weed competition in the first 3-4 months. Therefore, weed control involves cultural, biological, chemical and integrated control. For good growth and yield, cassava requires friable, light textured and well drained soils containing sufficient moisture and a balanced amount of nutrients. Farmers usually intercrop cassava with maize, melon, and other crops. Farmers can harvest cassava from 7 months after planting, however, most cassava varieties attain optimum weight and starch content 18 months after planting. Improved varieties selected for early bulking may be harvested after 6 months and attain maximum yield at 9-12 months.